Seasonal and Regional Distributions, Degree-Day Models, and Phoresy Rates of the Major Sap Beetle (Coleoptera: Nitidulidae) Vectors of the Oak Wilt Fungus, Bretziella fagacearum, in Wisconsin. Issue 5 (14th June 2018) - Jagemann, Stephanie M; Juzwik, Jennifer; Tobin, Patrick C; Raffa, Kenneth F
Abstract: Oak wilt is a lethal disease caused by the invasive fungus Bretziella fagacearum, which is transmitted belowground via root grafts and aboveground by sap beetles (Nitidulidae). Attempts to limit spread and impact of B. fagacearum emphasize limiting harvesting and pruning to periods of vector inactivity. However, there is limited information on sap beetle activity periods, responses to temperature, and phoresy frequencies of fungi. We sampled two major vectors in Wisconsin, Colopterus truncatus and Carpophilus sayi, for 2 yr to quantify their seasonal and geographic abundances. Trapping was performed in 12 oak stands, and beetles were assayed for B. fagacearum . C. truncatus was captured from March until November, peaking during April and May . C. sayi was captured from April until November, peaking in May and July. Relative abundances ( N = 15, 980) were 59.3% C. truncatus and 40.7% C. sayi. C. sayi was more abundant in southern Wisconsin, whereas C. truncatus was more evenly distributed. Both species were present at asymptomatic sites. All sites with oak wilt centers yielded beetles with viable fungal propagules, with the frequency of association ranging from 1 to 50%. Sites asymptomatic for oak wilt contained both beetle species, but no vector-borne viable pathogen. Degree-day models were constructed to improve the generality of these results and estimate cumulative emergences across a latitudinal range over the previous 10-yr means and extremes. Because activity by C. truncatus and C. sayi spans the seasonal activities of oak wilt vectors, these results can help guide oak management practices.